Phenylketonuria and Hirschsprung Disease-A Report of an Unusual Neonatal Presentation - Nina Lenherr; Viktoria A. Pfeifle; Stefan Holland-Cunz; Susanna H. M. Sluka; Beat Thöny; Gabor Szinnai; Martina Huemer; Marianne Rohrbach; Ralph Fingerhut (MDPI AG, 2017)
We describe a term born boy of non-consanguineous Swiss parents with tetrahydrobiopterine (BH4)-responsive Phenylketonuria (PKU) and Hirschsprung disease with unusual neonatal presentation. The child presented with floppiness, irritability, recurrent bilious vomiting and failure to pass meconium until 32 hours after birth, resulting in the clinical suspicion of an intoxication-type metabolic disease such as maple syrup urine disease (MSUD). Although the slightly elevated branched-chain amino acids in newborn screening on the fourth day of life initially supported the clinical suspicion of MSUD, the elevated Phenylalanine (Phe) of 650 µmol/L, low Tyrosine (Tyr) of 30 µmol/L, and a Phe/Tyr ratio of 22, led to the diagnosis of PKU. BH4-testing resulted in a significant decrease of Phe from 1011 to 437 µmol/L within 24 h. Urinary pterins and dihydropteridine reductase (DHPR) activity were normal, supporting the diagnosis of BH4-responsive PKU. Dietary restriction of Phe was initiated immediately, but oral feeding turned out to be difficult because of gastrointestinal symptoms. Intestinal motility disorder was suspected due to distended abdomen, obstructive symptoms and radiological findings with dilated intestinal loops and lack of intestinal gas in the anorectal region. Hirschsprung disease was confirmed by rectal suction biopsies and treated by a laparoscopically-assisted transanal pull-through (de la Torre) procedure. The boy is additionally compound heterozygous for two mutations in the phenylalanine hydroxylase (PAH) gene, which confirmed BH4-responsive PKU. It is the first case to be described in the literature of the comorbidity of PKU and Hirschsprung disease.